TO STUDY THE EFFECT OF AGILITY AND PERTURBATION EXERCISES VERSUS DYNAMIC RESISTANCE EXERCISES TO IMPROVE KNEE FUNCTION IN KNEE OSTEOARTHRITIS A COMPARATIVE STUDY (International Journal of Physiotherapy, 2015)
Background: Primary osteoarthritis is more commonly found in post menopausal women; Secondary osteoarthritis had an underlying cause such as trauma, obesity or inflammatory arthritis. It is characterized by a progressive degeneration of the articular cartilage with subsequent remodeling and hypertrophy of the bone at the joint margins. Muscle weakness is associated with increased functional limitation, disability. Muscle strengthening through resistance exercises increases physical function; decreases pain due to osteoarthritis and reduces self reported disability. Agility is the ability to change direction and maintain stability and is more often important in changing direction and speed; In order to train muscle to react quickly neuromuscular training is essential; Perturbation enhances the ability of the proprioceptor signals to the muscle and prevent injuries and enhances performance. The aim of this study is to compare the effectiveness of agility training and dynamic resistance training in patients with primary osteoarthritis.Methods: 50 subjects were assigned in two groups 25 each group and subjects were selected by convenient sampling method. Group A with agility training and Group B with dynamic resistance training. The treatment session was performed 3 days a week for 3 weeks lasting for 45minutes. Day 0 is the starting day of the session and Day-21 last day of the session. Each subject performed all the measurement with knee function assessed by Timed up and Go test (TUG) and Lower extremity function Scale (LEFS). Both outcomes were tested at starting day and at the end of 21st day.Results: All the analysis was carried out in PASW version 21.0. An alpha level of 0.05 was used to determine statistical significance. The between group analysis of agility training and dynamic strengthening for LEFS and TUG in evaluation of knee function was done using independent ‘t’ test showed statistically very significant (P=0.000).Conclusions: The effectiveness of Agility and Perturbation exercises improvement was considerably more than Dynamic resistance exercises. Therefore it is concluded that Agility and perturbation exercises is a better treatment approach than Dynamic resistance exercises.